Konsep Pengaturan Pertanggungjawaban Perawat Praktik Mandiri sebagai Upaya Pembaruan Hukum Kesehatan: Suatu Kajian Yuridis Normatif - Azriel Eko Firmansyah; Yovita Arie Mangesti (STIH Zainul Hasan Kraksaan Kraksaan, 2026)
In independent practice, nurses are vulnerable to malpractice resulting in patient harmsuch as performing medical procedures without written delegation. Although no specific regulation exists, a nurse’s legal liability can be pursued under criminal, civil, and administrative law. This study seeks to develop a regulatory framework for the accountability of Independent Practice Nurses as part of health law reform, thereby providing legal certainty and protection for patients and clear guidance for nurses.The research employs a normative‑juridical method based on library research, utilizing both the statute approach and the conceptual approach to examine the regulation of nurses’ legal accountability in independent practice. The findings indicate that service standardization by Independent Practice Nursesthrough adherence to the code of ethics, professional standards, service standards, and standard operating procedures (SOPs)—is crucial for ensuring care quality and patient safety. Administratively, independent practice is valid only with a current STRP and SIPP (Article 263 of Law No. 17/2023 on Health; Minister of Health Regulation No. 26/2019) and clinical authority as regulated by Government Regulation No. 28/2024. Under criminal law, negligence causing patient harm incurs personal liability, while under civil law, failure to fulfill the therapeutic agreement may constitute a tort (Articles 1365–1367 of the Civil Code) requiring compensation.